2000
DOI: 10.1086/309502
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Profiles of Accretion Disks around Rapidly Rotating Neutron Stars in General Relativity and the Implications for Cygnus X‐2

Abstract: We calculate the temperature profiles of (thin) accretion disks around rapidly rotating neutron stars (with low surface magnetic fields), taking into account the full effects of general relativity. We then consider a model for the spectrum of the X-ray emission from the disk, parameterized by the mass accretion rate, the color temperature and the rotation rate of the neutron star. We derive constraints on these parameters for the X-ray source Cygnus X-2 using the estimates of the maximum temperature in the dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 35 publications
(43 reference statements)
6
57
0
Order By: Relevance
“…(6) The two different situations, viz., rISCO > R and rISCO < R (rISCO is ISCO radius) have important consequences for observed X-ray features, and hence on the measurements of compact star parameters (e.g., Bhattacharyya (2011)). In the former situation, the length of the gap between rISCO and R is also very important for the X-ray emission, because the boundary layer emission to the accretion disc emission ratio depends on this length (e.g., Bhattacharyya et al (2000)). We find that rISCO is greater than R for the maximum mass and maximum angular momentum configurations, and the gap-length for EoS 1-2 is somewhat lower than that for EoS 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(6) The two different situations, viz., rISCO > R and rISCO < R (rISCO is ISCO radius) have important consequences for observed X-ray features, and hence on the measurements of compact star parameters (e.g., Bhattacharyya (2011)). In the former situation, the length of the gap between rISCO and R is also very important for the X-ray emission, because the boundary layer emission to the accretion disc emission ratio depends on this length (e.g., Bhattacharyya et al (2000)). We find that rISCO is greater than R for the maximum mass and maximum angular momentum configurations, and the gap-length for EoS 1-2 is somewhat lower than that for EoS 3.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a measurement of I of the binary pulsar J0737-3039A with 10% accuracy has been talked about (Morrison et al 2004). Apart from R/rg, R and I, [r orb − R] of LMXBs, which can be inferred from spectral and timing studies of observed X-ray emission (e.g., Bhattacharyya et al (2000)), also has a significant difference (≈ 98%) between EoS 2 and EoS 3. Therefore, since MG and ν have been measured for a number of compact stars (see § 1), B eff could be constrained from observations, within the ambit of our EoS models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We take the temperature of the accretion disk to decrease with radius as (e.g., LyndenBell 1969; Bhattacharyya et al 2000):…”
Section: Numerical Modelmentioning
confidence: 99%
“…Sibgatullin & Sunyaev (1998) analyzed the effect of the quadrupole component in the mass distribution of a rapidly rotating neutron star, on the energy release in the equatorial (or boundary) layer on the surface of the accreting star and in the accretion disc in the cases where the stellar radius is smaller (or larger) than the radius of the last stable circular orbit. The temperature profiles of (thin) accretion discs around rapidly rotating neutron stars (with low surface magnetic fields), taking into account the full effects of general relativity were obtained in Bhattacharyya et al (2000). The calculations suggest that the neutron star in Cygnus X-2 rotates close to the centrifugal mass-shed limit.…”
Section: Introductionmentioning
confidence: 99%